Atrial Functional Tricuspid Regurgitation: Novel Definition and Impact on Prognosis - Schlotter, Florian; Dietz, Marlieke F.; Stolz, Lukas; Kresoja, Karl-Patrik; Besler, Christian; Sannino, Anna; Rommel, Karl-Philipp; Unterhuber, Matthias; von Roeder, Maximilian; Delgado, Victoria; Thiele, Holger; Hausleiter, Jörg; et al. (Circulation. Cardiovascular interventions, 2022)
Atrial functional tricuspid regurgitation (atrial TR) has received growing recognition as a TR entity with a distinct cause owing to its independence from valvular tethering as the predominant mechanism underlying TR. However, characterization of atrial TR varies, and a universal definition is lacking. In total, 651 patients with significant functional TR were analyzed, including 438 conservatively treated individuals and 213 patients who received transcatheter tricuspid valve repair (TTVR). Based on a clustering approach, we defined atrial TR as tricuspid valve (TV) tenting height ≤10 mm, midventricular right ventricular diameter ≤38 mm, and left ventricular ejection fraction ≥50%. Patients with atrial TR were more often females, had higher right ventricular fractional area change, higher left ventricular ejection fraction, and lower LV end-diastolic diameter, TV tenting area and height, lower right ventricular and tricuspid annular size, enlarged, but lower right atrial area and lower TV effective regurgitant orifice area (all <0.05). Patients with atrial TR had significantly better long-term survival than non-atrial TR in the conservatively treated TR cohort ( <0.01, n=438). Atrial TR was independently associated with a lower rate of the combined end point of mortality and heart failure hospitalization at 1-year follow-up in the TTVR cohort (hazard ratio, 0.39; <0.05, n=213). TR degree was significantly reduced after TTVR in non-atrial and atrial TR ( <0.01). Functional parameters significantly improved following TTVR independent of TR cause ( <0.05). An echocardiography-based atrial TR definition is associated with prognostic relevance in patients with functional TR in conservatively treated TR and after TTVR.